Evaluation And Design Of User Interface To Improve User Experience Using Heuristic Evaluation And Human-Centered Design Methods On The BINUS E-Library And Knowledge Center Website - Khalda, Nibraz; Putra, Ditiofernal; Esa Putra , Rizky (International Journal Labs, 2025)
The Library and Knowledge Center (LKC) is one of BINUS University's units with two functions, the library itself and the knowledge center as a supporter of learning, research, and community service. LKC has a website that serves as an e-library (http://library.binus.ac.id), however the website copyright was in 2011, which means that the last website development was about 11 years ago. As a result, some of the existing features and design will need to be updated. In web design, User Interface (UI) and User Experience (UX) are important factors to ensure users can use it comfortably. The usability of LKC's website had to be re-evaluated in order to comply with good UX principles and determine the success rate of the UI implemented that meets user needs. The goal of this research is to identify usability problems on the e-library using Heuristic Evaluation while simultaneously designing a design solution using the Human-Centered Design method based on evaluator feedback, severity ratings, and Google Material Design (guidelines). Based on the heuristic evaluation method by Nielsen it was found that the 10 aspects studied obtained severity ratings of 0 (1 aspect), 1 (6 aspects), 2 (2 aspects), and 3 (1 aspect). Then, a prototype of the design solution is made based on the advice of the evaluator, severity ratings, and Google Material Design (guidelines). The result is comparative analysis between existing design and solution design from the UI and UX perspectives that can be taken into consideration to improve the LKC’s website.